The case for cancellation - George C. Abbott (Intereconomics, 1975)
Given the chronic and crippling impact which their mounting international indebtedness exerts on the economies of many developing countries, cancellation on a fairly comprehensive basis seems the only realistic way of coping with this problem. According to the author, the existing objections to a write-off are mainly emotional and psychological and refuse to recognise that relationships have changed.
Keywords: 330; Debt Consolidation